Emission of short-lived halocarbons by three common tropical marine microalgae during batch culture - Lim, Yong Kian; Phang, Siew Moi; Sturges, William T.; Malin, Gill; Abd Rahman, Noorsaadah (Springer Verlag, 2018)
Very short-lived halocarbons of marine biogenic origin play an important role in affecting tropospheric and stratospheric chemistry. In recent years, more attention has been paid to tropical regions where the influence of strong convective forces is responsible for rapid uplifting of the volatile organohalogens from the open surface waters into the atmosphere. This laboratory-based study reports on three common tropical marine microalgae capable of emitting a range of short-lived halocarbons, namely, CH3I, CHBr3, CH2Br2, CHBr2Cl, and CHCl3. Chlorophyll a and cell density were highly correlated to the quantity of all five compounds emitted (p < 0.01). The diatom Amphora sp. UMACC 370 had a higher range of CH3I emission rate (10.55–64.18 pmol mg−1 chl a day−1, p < 0.01) than the cyanobacterium Synechococcus sp. UMACC 371 and chlorophyte Parachlorella sp. UMACC 245 (1.04–3.86 pmol mg−1 chl a day−1 and 0–2.16 pmol mg−1 chl a day−1, p < 0.01, respectively). Furthermore, iodine was the dominant halogen emitted in terms of total combined halide mass of all three species. Overall, the emissions of short-lived halocarbons were both species- and growth phase-dependent, highlighting the importance of considering cell physiological conditions when determining gas emission rates.